TINJAUAN NAFKAH REKREASI PERSPEKTIF PENGHULU DI KOTA PALANGKA RAYA - Saudah Saudah; Eka Suriansyah; Baihaki Baihaki (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
The research was motivated by age development that caused by advancement of science and technology so make change and increase in needs, like family needs and one of in it is recreation need even though this need didn’t explain in Islamic law or Indonesia. Research objectives are to know how the position of recreation needs from Islamic law and to know the perspective from Penghulu in Palangka Raya about recreation needs. This research used an empirical juridical and socio-legal approach. Data collection techniques used interviews, observation, and documentation. While research subjects were five Penghulu in Palangka Raya. There were four theories that used in this research such as modernization, needs, perception, and maqāṣid asy-syarīʿah theory. The results; (1) Position of recreation needs in Islamic law is not included in obligatory needs because not explained specifically in Al-Qur’an or laws which exist in Indonesia. But according to explanation from the subjects and recreation needs on modern society therefore recreation needs were secondary needs because it is not obligatory or primary needs. (2) There were two perspectives from Penghulu about recreation needs, first, they stated that recreation needs income is in accordance with the situation, namely recreational income which, if the situation allows, then recreation is carried out without any demands or recreational needs, and recreational income according to conditions, namely conditions where recreational income is needed.